THE POTENTIAL OF CIRCULARITY IN THE DEVELOPMENT OF THE UPSTREAM-DOWNSTREAM COFFEE AGROINDUSTRY TO FOSTER A GREEN ECONOMY AND ENHANCE CLIMATE RESILIENCE (Jurnal Teknologi Industri Pertanian, 2026)
As a cornerstone of sustainable development, the circular economy offers a robust mechanism for addressing climate change by maximizing resource utility and minimizing the environmental footprint of agro-industrial processes. This study evaluates the prevalence of linear production pattern within small coffee agro-industries and explores the transition toward a competitive, sustainable system through circular economy principles. Focused on the Ketakasi Cooperative in the Silo District of Jember Regency, the research utilizes a multi-methodological approach – incorporating the Material Circularity Indicator (MCI), the 9R framework, and impact analysis to assess circularity potential. Findings reveal that the cooperative currently operates on predominantly linear model, evidenced by MCI of 0.223. However, substantial potential for circularity exists through the conversion of coffee waste into compost, liquid fertilizer, briquettes, animal feed, and value-added products from defective beans. The 9R analysis demonstrates that implementation of reducing, reusing, and recycling strategies is economically viable, yielding a Net Benefit/Cost ratio greater than1and a payback period less than six months. These results suggest that adopting circular principles can significantly foster a green economy while enhancing climate change resilience within the coffee agro-industrial sector. This research fills a critical gap by offering a site-specific circular economy model for the coffee industry that balances environmental sustainability with immediate economic profitability through innovative waste repurposing.Keywords: circular economy, coffee agroindustry, green economy, Ketakasi Cooperative, resilience